Kemuridan dan Karakter Wanita Samaria: Ditinjau dari Perspektif Injil Yohanes - Agustinus Abraham (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
This study explores the discipleship and character of the Samaritan woman as portrayed in the Gospel of John. The background emphasizes that discipleship is not merely about listening to Jesus’ teachings but involves a personal relationship, obedience, and life transformation. The Gospel of John offers a unique perspective by presenting that Christ’s disciples are not limited to men but also include women, as illustrated in the narrative of the Samaritan woman at the well. This research employs a qualitative method with a literature review approach, focusing on biblical texts and relevant studies. The findings reveal that the discipleship process of the Samaritan woman demonstrates a progressive transformation: from initial skepticism to faith and recognition of Jesus as the Messiah. This transformation unfolds through three key dimensions: the dialogue on living water, the understanding of true worship, and the testimony shared with her community. The Samaritan woman emerges as a genuine disciple through her faith, courageous witness, and role as Christ’s representative in proclaiming universal salvation. Her notable traits include openness, honesty, curiosity, courage, and willingness to change. The study highlights that the Gospel of John portrays discipleship as inclusive, affirming the role of women as models of faith. Its implications provide theological insight into the equality of disciples in Christ and offer relevance for today’s church in fostering participatory and transformative faith communities.